Respostas
respondido por:
1
2( 7 x + 2 ) + 12 ( x + 1 ) = 2
14 x+ 4 + 12 x + 12 = 2
14 x + 12 x + 12 + 4 = 2
26 x + 16 = 2
26 x = 2 - 16
26 x = -14
x = -14/26
14 x+ 4 + 12 x + 12 = 2
14 x + 12 x + 12 + 4 = 2
26 x + 16 = 2
26 x = 2 - 16
26 x = -14
x = -14/26
respondido por:
0
2 (7x + 2) + 12 ( x+ 1) = 2
14x + 4 + 12x + 1 = 2
26x + 5 = 2
26x = -3
x = -3/26
14x + 4 + 12x + 1 = 2
26x + 5 = 2
26x = -3
x = -3/26
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás